2020
DOI: 10.1002/col.22573
|View full text |Cite
|
Sign up to set email alerts
|

The development of color of historic buildings on the North Bund of Shanghai

Abstract: The North Bund is located in the southern riverside of Hongkou District, Shanghai, characterized by rich historical architecture. The yellows make up a large proportion, followed by the reds and neutrals. The auxiliary and interspersed colors center round the reds, neutrals, followed by the yellows. Dominant and auxiliary colors fall into the category of high and mid‐high brightness and the interspersed colors of low and mid‐low brightness. The color development of the historical buildings on the North Bund ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The dominant color features determine landscapes' presentation and visual experience [24]. Urban tones are the overall effect constructed by the three colors and their combined relationships [28], as follows:…”
Section: Elements Of Color Landscapementioning
confidence: 99%
“…The dominant color features determine landscapes' presentation and visual experience [24]. Urban tones are the overall effect constructed by the three colors and their combined relationships [28], as follows:…”
Section: Elements Of Color Landscapementioning
confidence: 99%
“…The developed urban sub-centers have higher color saturation than their surrounding areas. The brightness of urban construction areas is lower than that of rural areas, with obvious differences between urban and rural areas [28]. Many studies addressing urban colors have been conducted in different areas in Shanghai.…”
Section: Street Function and Urban Color Distributionmentioning
confidence: 99%
“…Chin offered support technology for designing urban scenes based on hierarchical scene structure, which can identify the current circumstances of outdoor urban scenes and produce a colour composition evaluation 44 . Wang et al conducted multi‐directional research on the colour(s) of historic buildings in the North Bund of Shanghai, including colour development, 45 selection preferences, 46 and colour fragmentation 47 . We found that colour planning evaluation objects, residents' living standards, and overseas experience all influence the implementation evaluation of colour planning.…”
Section: Literature Reviewmentioning
confidence: 99%